2018
DOI: 10.1042/bcj20170899
|View full text |Cite
|
Sign up to set email alerts
|

Adipose depot-specific effects of ileal interposition surgery in UCD-T2D rats: unexpected implications for obesity and diabetes

Abstract: Ileal interposition (IT) surgery delays the onset of diabetes in a rat model of type-2 diabetes (UCD-T2DM). Here, to gain a deeper understanding of the molecular events underlying the effects of IT surgery, we examined the changes in the proteome of four white adipose depots (retroperitoneal, mesenteric, inguinal, and epididymal) and plasma-free fatty acid profile in pre-diabetic rats 1.5 months following IT or sham surgery. The IT-mediated changes were exerted mainly in mesenteric fat and spanned from delayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…S13) in any of the enzymatic activities tested (including CCO). This indicated that IT surgery is likely to have a relatively short-term effect (14) as we previously reported for endoplasmic reticulum stress response mitigation and adipose tissue remodeling after IT surgery (11).…”
Section: It Surgery Impacts Cholesterol and Sterol Syntheses And Attesupporting
confidence: 71%
See 3 more Smart Citations
“…S13) in any of the enzymatic activities tested (including CCO). This indicated that IT surgery is likely to have a relatively short-term effect (14) as we previously reported for endoplasmic reticulum stress response mitigation and adipose tissue remodeling after IT surgery (11).…”
Section: It Surgery Impacts Cholesterol and Sterol Syntheses And Attesupporting
confidence: 71%
“…Recently, we reported that IT surgery had a more profound and prolonged effect on mesenteric fat depot than the other adipose depots that were studied (inguinal, epididymal, or retroperitoneal) (11). This specific effect on mesenteric adipose tissue was associated with changes that would be expected to ensue in a delay in the maturation of adipocytes (11).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Adipose tissues are known to preserve food-derived lipids as excess energy and function as an endocrine organ for energy homeostasis by secreting related hormones [ 1 ]. Dysfunction of the physiological roles of adipose tissues occurs with an expanded mass of white adipocytes (WAs) that subsequently induce human obesity [ 2 ]. In contrast, brown adipocytes (BAs) were discovered to execute non-shivering thermogenesis by dissipating stored lipid droplets in small rodents and infants [ 3 ].…”
Section: Introductionmentioning
confidence: 99%